Axing the Rainbow - Irina Turner (Modern Africa, 2019)
Today, the Rainbow Nation as the central metaphor for postapartheid South Africa falls short of serving as a unifying identification marker due to its tendency to gloss over contrasting living realities of diversified identities and ongoing systemic discrimination. The South African Fallism movements – the student-driven protests against neocolonial structures in academic institutions – spearheaded public criticism with the current state of ongoing social disparity in South Africa and revived the critique of so-called rainbowism, i.e., the belief that a colour-blind society can be created. In an application of Critical Discourse Analysis focusing on mythical metaphors, this article asks to what extent the new president Cyril Ramaphosa in his maiden State of the Nation Address projected a post-Zuma South African nation and answered to the challenges posed by Fallists.